Amazon Submarine Fan Drilling: A Big Step Forward For Deep-sea Fan Models - Hiscott, Richard; Pirmez, Carlos; Flood, Roger (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1997)
Summary The results of coring on the Amazon sub-marine fan in 1994 challenge previous ideas about faciès architecture and genesis of fan deposits. A shingled set of latest Pleistocene, upward-fining channel-levee units is underlain by, and locally interleaved with, equally voluminouss and-rich deposits. The sands occur as 5-25 nv thick packets, locally rich in semi-consolidated mud clasts. Each sand-richunit is inferred to have been partly derived from an upfan avulsion site, land-ward of which entrenchment of the pre-existing channel floor occurred. Sandswere distributed into the adjacent inter-channel low, where lack of confinement allowed spreading of turbidity currents to form sheet-like sand-rich bodies. Subsequently, the advance of a new leveed channel over the sheet sands focusseds and transport along the channel axis, with simultaneous accumulation of muddy overbank deposits in the levees. Ancient channel-levee systems atop sheet sands, including those in some oilfields, may have similarly formed during single lowstands of sea level and as a result of repeated cycles of levee progradation and upfan avulsion.